Understanding the effect of cognitive/brain reserve and depression on regional atrophy in early Alzheimer's disease. Issue 7 (3rd October 2019) - Capogna, Elettra; Manca, Riccardo; De Marco, Matteo; Hall, Anette; Soininen, Hilkka; Venneri, Annalena
ABSTRACT: Introduction : Depression in patients with mild cognitive impairment (MCI) and dementia of the Alzheimer's type (AD) is associated with worse prognosis. Indeed, depressed MCI patients have worse cognitive performance and greater loss of gray-matter volume in several brain areas. To date, knowledge of the factors that can mitigate this detrimental effect is still limited. The aim of the present study was to understand in what way cognitive reserve/brain reserve and depression interact and are linked to regional atrophy in early stage AD. Methods : Depression was evaluated with the Patient Health Questionnaire-9 in 90 patients with early AD, and a cutoff of ≥ 5 was used to separate depressed ( n = 44) from non-depressed ( n = 46) patients. Each group was further stratified into high/low cognitive reserve/brain reserve. Cognitive reserve was calculated using years of education as proxy, while normalized parenchymal volumes were used to estimate brain reserve. Voxel-based morphometry was carried out to extract and analyze gray-matter maps. 2 × 2 ANCOVA s were run to test the effect of the reserve-by-depression interaction on gray matter. Age and hippocampal ratio were used as covariates. Composite indices of major cognitive domains were also analyzed with comparable models. Results : No reserve-by-depression interaction was found in the analytical models of gray matter. Depression was associated with less gray matter volume in the cerebellum and parahippocampal gyrus. The brain reserve-by-depression interaction was a significant predictor of executive functioning. Among those with high brain reserve, depressed patients had poorer executive skills. No significant results were found in association with cognitive reserve. Conclusion : These findings suggest that brain reserve may modulate the association between neurodegeneration and depression in patients with MCI and dementia of the AD type, influencing in particular executive functioning.